2008
DOI: 10.1038/sj.gt.3303094
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Aβ-induced cognitive impairment by ultrasound-mediated gene transfer of HGF in a mouse model

Abstract: A new therapeutic approach to treat Alzheimer's disease (AD) is needed, and the use of growth factors is considered to be a candidate. Hepatocyte growth factor (HGF) is a unique multifunctional growth factor, which has the potential effect to exert neurotrophic action and induce angiogenesis. In this study, we examined the effects of overexpression of human HGF plasmid DNA using ultrasound-mediated gene transfer into the brain in an Ab-infused cognitive dysfunction mouse model. We demonstrated that HGF gene tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…38, 39 Its expression continues in adulthood and it is induced by ischemic injury 40 and other disease processes, including AD. 41 HGF enhances long-term potentiation, 42 improves or attenuates ischemia-related memory deficits 43 and Aβ-induced behavioral impairment, 44 and has anxiolytic properties, 45 whereas its suppression increases anxiety and depressive behaviors in rodents. 46 To our knowledge, only two studies have investigated HGF in relation to depression in humans, one of which found significantly lower serum HGF levels among 26 people with major depression compared with 19 controls, 47 whereas the other study found no difference in HGF levels in 12 women with major depression and borderline personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…38, 39 Its expression continues in adulthood and it is induced by ischemic injury 40 and other disease processes, including AD. 41 HGF enhances long-term potentiation, 42 improves or attenuates ischemia-related memory deficits 43 and Aβ-induced behavioral impairment, 44 and has anxiolytic properties, 45 whereas its suppression increases anxiety and depressive behaviors in rodents. 46 To our knowledge, only two studies have investigated HGF in relation to depression in humans, one of which found significantly lower serum HGF levels among 26 people with major depression compared with 19 controls, 47 whereas the other study found no difference in HGF levels in 12 women with major depression and borderline personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…found that HGF gene transfer alleviated amyloid-β-induced cognitive impairment in mice, as evaluated by a behavioral test. 122) …”
Section: Therapeutic Significance Of Hgf For the Rescue Of Intractablmentioning
confidence: 99%
“…[3][4][5][6][7] Moreover, it is suggested to regulate neuronal survival and seemed to be useful for AD treatment, considering the studies like showing gene transfer of HGF in a mouse model alleviate amyloid β induced cognitive impairment. 10) So, pharmacological approach including gene therapy to increase the HGF level in the brain is going on. Thus, HGF inducers may also be useful as therapeutic agent for AD treatment.…”
Section: Resultsmentioning
confidence: 99%
“…9) HGF is also thought to be useful for Alz heimer's disease (AD) therapy according to the recent study showing that gene transfer of HGF in a mouse model alleviate amyloid β induced cognitive impairment. 10) Thus, HGF may be useful for curing for intractable diseases including neurodegenerative diseases, and its inducers may also be useful as therapeutic agent. For example, interleukin-1, one of growth factors such as epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) are known to induce HGF production.…”
mentioning
confidence: 99%
See 1 more Smart Citation